Dropout rates in couples undergoing in vitro fertilization and intrauterine insemination. (October 2016) - Bensdorp, Alexandra J.; Tjon-Kon-Fat, Raissa; Verhoeve, Harold; Koks, Carolien; Hompes, Peter; Hoek, Annemieke; de Bruin, Jan Peter; Cohlen, Ben; Hoozemans, Diederik; Broekmans, Frank; van Bomme, Peter; Smeenk, Jesper; et al.
Abstract: Objective: To compare dropout rates in couples undergoing conventional in vitro fertilization with single embryo transfer (IVF-SET), in vitro fertilization in a modified natural cycle (IVF-MNC) or intrauterine insemination with ovarian stimulation (IUI-OS). Study design: Secondary analysis of a multicentre randomized controlled trial between January 2009 and February 2012. 602 couples with unexplained or mild male subfertility, allocated to IVF-SET ( N  = 201), IVF-MNC ( N  = 194) and IUI-OS ( N  = 207). Main outcome measures: Dropouts, defined as couples who discontinued their allocated three cycles of IVF-SET, six cycles of IVF-MNC or IUI-OS, without having achieved a pregnancy. We classified dropouts as "following medical advice" or "patient initiated". Result(s): Thirty couples (15%) allocated to IVF-SET dropped out and 45 couples (23%) allocated to IVF-MNC, compared to 26 couples (13%) allocated to IUI-OS; relative risk (RR) 1.2 (95%CI; 0.73–1.9) for IVF-SET and 1.9 (95%CI; 1.2–2.9) for IVF-MNC, both compared to IUI-OS. Nine couples (4.5%) allocated to IVF-SET, 14 (7.2%) allocated to IVF-MNC and 14 (6.8%) allocated to IUI-OS dropped out following medical advice; RR of 0.51 (95%CI; 0.21–1.2) for IVF-SET and 0.84 (95%CI; 0.39–1.80) for IVF-MNC, both versus IUI-OS. Twenty-one couples (10%) allocated to IVF-SET were patient initiated dropouts, as were 31 (16%) allocated to IVF-MNC and 12 (5.8%) allocated to IUI-COS; RR 1.8 (95%CI; 0.91–3.6) for IVF-SET and 2.8 (95%CI; 1.5–5.2) for IVF-MNC both versus IUI-OS. Conclusion(s): IVF-SET and IUI-OS result in comparable drop-out rates, while drop-out rates after IVF-MNC are almost twice as high, mainly driven by patient preferences.